2007
DOI: 10.1007/s11664-006-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Annealing and Measurement Temperature Dependence of W2B- and W2B5-Based Rectifying Contacts to p-GaN

Abstract: metallization schemes was investigated using x-ray photoelectron spectroscopy (XPS), current-voltage (I-V), and Auger electron spectroscopy measurements. The Schottky barrier height (SBH) determined from XPS is 2.71 eV and 2.87 eV for as-deposited W 2 B-and W 2 B 5 -based contacts, respectively. By comparison, fitting of the I-V curves using the thermionic field emission model gives unphysical SBHs > 4 eV due to the presence of an interfacial layer acting as an additional barrier to carrier transport. Upon ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Sawada et al 12 suggested that these additional currents seem to modify the TE current and apparently lower the Schottky barrier height from J-V measurements. Stafford et al 32 and Voss et al 33 used a similar approach to analyze the I-V characteristics of boride-based contacts on p-type GaN.…”
Section: ͑4͒mentioning
confidence: 99%
“…Sawada et al 12 suggested that these additional currents seem to modify the TE current and apparently lower the Schottky barrier height from J-V measurements. Stafford et al 32 and Voss et al 33 used a similar approach to analyze the I-V characteristics of boride-based contacts on p-type GaN.…”
Section: ͑4͒mentioning
confidence: 99%